Pharmacokinetic interactions between rifampicin and efavirenz in HIV-TB coinfections - Yenny, Yenny (Universa Medicina, 2009)
The increased percentage of patients with HIV-TB coinfection leads to inevitable interactions between rifampicin and efavirenz. Efavirenz is a potent non-nucleoside reverse transcriptase inhibitor (NNRTI) for the treatment of HIV infection. The use of this drug combination with rifampicin causes problems in determination of the optimal dosage of efavirenz when administered concomitantly with rifampicin. Efavirenz is metabolized by the enzyme cytochrome P-450 (CYP), i.e. the CYP2B6 and CYP3A4 isozymes, of which rifampicin is an inducer. The induction of cytochrome P-450 by rifampicin is mediated by pregnane X (PXR) and constitutive androstane receptors (CAR) in the cell nucleus, resulting in a wide variation in the plasma efavirenz concentrations, such that a therapeutic failure or the occurrence of toxic effects are to be expected. The optimal dosage of efavirenz is commonly determined through pharmacokinetic studies, but thisÂ  is problematic in the combined use of the drug with rifampicin, due to the wide variation in study design, method, and sample size of each study. Ethnic factors and genetic polymorphism of the enzymes that metabolize efavirenz contribute to the problem of determining the optimal dose of this drug. Pharmacokinetic studies with good measurement parameters and methods are still necessary as the basis for determining the optimal dose of efavirenz in the Indonesian population.